2014
DOI: 10.1002/hipo.22288
|View full text |Cite
|
Sign up to set email alerts
|

The anticoagulant activated protein C (aPC) promotes metaplasticity in the hippocampus through an EPCR-PAR1-S1P1 receptors dependent mechanism

Abstract: Thrombin and other clotting factors regulate long-term potentiation (LTP) in the hippocampus through the activation of the protease activated receptor 1 (PAR1) and consequent potentiation of N-methyl-d-aspartate receptor (NMDAR) functions. We have recently shown that the activation of PAR1 either by thrombin or the anticoagulant factor activated protein C (aPC) has differential effects on LTP. While thrombin activation of PAR1 induces an NMDAR-mediated slow onset LTP, which saturates the ability to induce furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 39 publications
2
33
0
2
Order By: Relevance
“…Interestingly, Maggio et al (2014) characterized aPC as a metaplastic molecule that enhances LTP upon delivery of a subthreshold stimulation. They propose a model in which upon binding to the endothelial protein C receptor, which is also expressed on astrocytes, aPC activates PAR1, which triggers the SphK-dependent production of S1P.…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
“…Interestingly, Maggio et al (2014) characterized aPC as a metaplastic molecule that enhances LTP upon delivery of a subthreshold stimulation. They propose a model in which upon binding to the endothelial protein C receptor, which is also expressed on astrocytes, aPC activates PAR1, which triggers the SphK-dependent production of S1P.…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
“…Using rodent models of mTBI and relevant cognitive and biological tests, numerous treatments with mechanism-based drug features have been reported to ameliorate mTBI induced cognitive deficits. As a recent example among many, we have lately shown that an increased thrombin concentration induced by mTBI may cause amnesia through the activation of its receptor, the proteases activated receptor 1 (PAR1) (Itzekson et al, 2014, Maggio et al, 2014); thereby exposing a novel therapeutic target potentially underpinning cognitive detriments of trauma. In the following sections, several widely used rodent models of mTBI are highlighted that can be combined with well characterized behavioral assays, epitomized by the novel object recognition (NOR) task for assessing cognitive deficits, to provide a methodological toolbox for evaluating molecular mechanisms involved in mTBI.…”
Section: Traumatic Brain Injurymentioning
confidence: 99%
“…Notably, PAR-1 knockout animals present with substantial impairments in hippocampus-dependent learning and memory processes (Almonte et al, 2007, 2013). In synopsis, PAR-1 has a key role in memory formation and synaptic plasticity (Maggio et al, 2013a,b, 2014), which can be regulated in a concentration-dependent manner by thrombin under physiological and pathological conditions. Interestingly, thrombin concentrations rise in the brain just a few minutes following a mTBI (Itzekson et al, 2014; Maggio et al, 2014), with such an increase in concentrations related to a poor NOR performance in animals challenged by brain trauma.…”
Section: Pharmaceutical Treatments For Weight Drop-induced Damage mentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacological evidence suggests that S1P and S1P 3 are associated with LTP formation (Maggio et al, 2014). However, S1P significantly increased eEPSC amplitudes and eEPSC decay times both in WT and in S1P3/ mice, suggesting an increase in glutamate release, and possibly a reduction in non-NMDA receptor desensitization.…”
Section: Discussionmentioning
confidence: 99%